A solid–liquid two-phase precipitation method for the growth of fullerene (C60) nanowires. Issue 36 (23rd August 2021) - Fan, Xiao; Geng, Junfeng; Soin, Navneet; Chakrabarti, Supriya; Mitra, Somak; Roqan, Iman S.; Li, Hua; Babatunde, Mustapha Olaoluwa; Baldwin, Andy
Abstract : A schematic diagram of the preparation of C60 nanowires by the solid–liquid two-phase precipitation method. Abstract : A novel solid–liquid two-phase precipitation (SLTPP) method, utilising a solidified ( via liquid N2 ) m -xylene solution of C60 with liquid isopropanol (IPA) as a counter-solvent, is proposed for the synthesis of fullerene (C60 ) nanowires. The resulting C60 nanowires were observed to possess high crystallinity and a length-to-diameter ratio of up to several thousands with a diameter as small as ∼85 nm. We further systematically investigated the effects of the C60 concentration (1–5.2 mg ml −1 ) and solvent–counter-solvent ratio (1 : 6–2 : 1) to optimise the growth conditions for high-quality, size-controlled C60 nanowires. A comparative study on the widely-used liquid–liquid interfacial precipitation (LLIP) method showed that the proposed SLTPP method led to a much narrower diameter distribution (414.20 ± 92.10 nm vs. 3237.20 ± 1790.30 nm for LLIP) across the studied range of the C60 concentrations and solvent–counter-solvent ratios, and is therefore considered to be a more stable and reliable synthesis route. We propose that the gradual melting of the m -xylene C60 solid-phase leads to slower diffusion of the solvent–counter-solvent medium, providing a much more stable interface for high-quality crystal growth.